COVID-19: Unveiling the Ethnoreligious Relations in Malaysia - Romzi Ationg; Azizan Had; Gaim Lunkapis (IJAST, 2020)
The Coronavirus disease 2019 (COVID-19) was first identified in December 2019 in Wuhan, the capital of China’s Hubei province. Since then this infectious disease has speeds globally, resulting the implementation a Movement Control Oder (MCO) in almost all, if not, all countries around the globe as a means of minimizing the spread of the disease. Apart from that, the imposition of MCO also is vital to diminishing panic among the global population, a situation ignited by the fact that the disease brings a significant impact to not only human health but also involves various areas of human life. In Malaysia, though the disease is mainly a medical issue, it also unveils the ethnoreligious relations among the population within the country. Nevertheless, even though scholars often described the ethnoreligious relations in this country as weakening, as of to date, examination on the ethnoreligious relations in Malaysia during the outbreak of such disease remain limited. Thus, explanation on what exactly is the present ethnoreligious relations among the citizens in this country during this shocking incident of pandemic respiratory disease linked to COVID-19 is inadequate. Therefore, using media reports analysis, this paper analyzes the ethnoreligious relations in this country that unveils during the outbreak of respiratory disease caused by COVID-19, and thus ascertain how actually the disease has unveils such phenomenon. This paper explores the prospects of a national improvement which focusing on either maintaining or consolidating an ethnoreligious harmony in this country regardless of what the situation they are encountering.